Role for Irrigation and Debridement in Periprosthetic Infections - Romanò, Carlo; Logoluso, Nicola; Drago, Lorenzo; Peccati, Andrea; Romanò, Delia (The Journal of Knee Surgery, 2014)
Irrigation and debridement (I&D) has been described as a possible option to eradicate early postoperative periprosthetic hip and knee infections, as well as late, acute, and hematogenous ones. Still, the literature fails to uniquely assess the effectiveness of this procedure and often provides conflicting evidence. To reconcile this difference, a systematic review of the available literature from 1970 to 2013 was undertaken. Fifteen articles, for a total of 796 patients, met the inclusion criteria; the average success rate was 44.9 and 52% after a single or repeated I&D procedures, respectively, at an average of 4 years follow-up. Despite the methodological differences and the heterogeneity of the material reviewed, this study demonstrates that this procedure only attains a relatively low success rate of infection eradication, depending on when patients are selected for surgical intervention according to the timeframe of their symptoms.
Keywords: hip; knee; prosthesis; infection; irrigation; debridement